Methyl Formate: an Experimental and Kinetic Study of its Oxidation at High-Pressure - Marrodán, Lorena; Millera, Ángela; Bilbao, Rafael; Alzueta, Mª Ujué (Jornada de Jóvenes Investigadores del I3A, 2017)
An experimental and kinetic modeling study of the influence of pressure on the oxidation of methyl formate (MF) has been performed in the 1-60 bar pressure range. The influence of stoichiometry, temperature, pressure and presence of NO on the conversion of MF, and on the formation of the main products, has been analyzed.